Attitude of the staff nurses toward COVID care and work challenges faced by them - Purnima Kundu; Binapani De; Lakhsmi Pandit (Wolters Kluwer Medknow Publications, 2023)
Background: At the beginning of pandemic, many of the nurses were scared of contracting COVID infection by themselves. The work of nurses during the pandemic was highly appreciated by the society though they worked with severe challenges. Hence, it was utmost necessary to explore the attitude of the nurses toward COVID care and what challenges they faced during caring for the COVID patients. Objectives: The main objectives of the study were to assess the attitude of the nurses toward working in COVID units, to identify the challenges faced by the nurses, and to find out the relationship between the nurses attitude and challenges. Methods: The study was carried out adopting descriptive survey design with 190 conveniently selected staff nurses working in the selected COVID care units of Kolkata and Bankura. Two self-developed rating scales were administered using self-reporting method to measure the attitude and challenges of the nurses. Results: All the staff nurses expressed their favorable (positive) attitude. Maximum (64.21%) of the staff nurses had a high level of challenges. A very weak positive correlation found between attitude of the staff nurses toward COVID care and challenges they faced (ρ = 0.197, P = 0.006). Computation of Chi-square test revealed that neither attitude nor challenges was influenced by any of the personal characteristics of the nurses. Conclusion: In spite of working with a high level of challenges, the majority of the nurses demonstrated favorable attitude toward taking care of COVID patients.